549 Prevention of Obesity Through Healthy Nutrition in the First Year of Life. (October 2012) - Neamtu, ML; Dobrota, L; Mehedintu, BI
Abstract : Background: Obesity, defined as excess body fat can be diagnosed at 6 months. In children, BMI percentiles are used, defining the overweight between 85–95 and obesity >95. The main predictors of primary obesity in infancy are high birthweight, parental obesity, low total energy expenditure and energy intake (EI). Aim: Calculation of optimal EI in infants. Method: Calculation of estimated energy requirements (EER) for infants was made according to the formulas: [(89×Gkg)-100]+175 between 0–3 months, [(89×Gkg)-100]+56, between 4–6 months, [(89×Gkg)-100]+22, between 7–12 months. Calculation of fluid requirements was made according to Apert formula: Gg /10+200(300). Results: Were studied 11 infants 7–9 months old with normal birthweight, without parental obesity, fed with formula (76kcal/100ml) from the first month, with diversification started from 4 months, eating high-caloric foods from 5 months (100kcal/100ml), fed according to Apert formula. Seven infants had weight above the 85 th percentile and 4 of them >95 th percentile. Comparing EI according to Apert formula with EER is found an excess, increased with the beginning of diversification. Disposal of high-caloric foods, feeding with formulas with a similar amount of calories as human milk (67kcal/100ml), feeding according to EER and fluid supplementation with low-caloric beverages have led to normalization of BMI percentiles of infants at the age of 12 months. Conclusions: EI is an important predictor of infant weight. It is necessary to use formulas with a similar amount of calories as human milk. Infant feeding according to EER and fluid supplementation with low-caloric beverages lead to a normal BMI.